An audit of iron therapy in patients with iron deficiency anemia in a tertiary care hospital - Natarajan, Anusha; Topno, Isabella (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Iron deficiency anemia (IDA) is a major nutritional problem globally, which is especially true in the developing countries like India. Even though the treatment is simple and effective, there is a high prevalence of IDA. The reason for this is partly due to non-compliance of the patients and partly due to ineffective or incomplete treatment by the physicians. Hence, the present study was done with the objective to study the treatment pattern in patients with IDA. Methods: This retrospective observational study was conducted in the Medical Records Department, Pondicherry Institute of Medical Sciences (PIMS), Puducherry for a period of 1-year with a sample size of 100 patients. Patients of all ages and either sex diagnosed to have mild to severe IDA were included in the study. The following data like: demographic details, hemoglobin, drugs used to treat the anemia, duration of treatment were obtained. The data will be presented as descriptive statistics. Results: Out of the 100 patients scrutinized 57% had severe IDA, 39% moderate IDA, and 4% had mild IDA. Of the 100 patients, 71% were females and 29% were males. For 14% of the patients, no treatment was given and for 19% of the patients treatment was given but the duration of treatment was not mentioned. Conclusions: The results of the present study showed that majority of the patients with IDA did not receive the recommended WHO treatment. The present study shows that even though the treatment of a common nutritional disorder-IDA is simple and effective, the prevalence of the same is high, and the majority of the patients are being undertreated. Patients should also be educated about the implications of the disorder and the importance of its treatment.